2016
DOI: 10.1103/physrevb.94.045111
|View full text |Cite
|
Sign up to set email alerts
|

Many-body localization and transition by density matrix renormalization group and exact diagonalization studies

Abstract: A many-body localized (MBL) state is a new state of matter emerging in a disordered interacting system at high energy densities through a disorder driven dynamic phase transition. The nature of the phase transition and the evolution of the MBL phase near the transition are the focus of intense theoretical studies with open issues in the field. We develop an entanglement density matrix renormalization group (En-DMRG) algorithm to accurately target the entanglement patterns of highly excited states for MBL syste… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
96
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(103 citation statements)
references
References 75 publications
7
96
0
Order By: Relevance
“…Furthermore, we mapped out the mobility edge in this model, demonstrating that the method has a good energy resolution. Our criterion requires a sample of adjacent eigenstates in an energy window, and hence it can be straightforwardly evaluated by "spectral transformation" methods applicable to much larger system sizes, either via iterative diagonalizations [24] or DMRG [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we mapped out the mobility edge in this model, demonstrating that the method has a good energy resolution. Our criterion requires a sample of adjacent eigenstates in an energy window, and hence it can be straightforwardly evaluated by "spectral transformation" methods applicable to much larger system sizes, either via iterative diagonalizations [24] or DMRG [48][49][50][51].…”
Section: Discussionmentioning
confidence: 99%
“…However, since the number of eigenstates is exponential in the system size, for large N one can only tackle the eigenstates in a certain energy window using MPS (see, e.g., Refs. [49][50][51]). On the other hand, spectral tensor networks are meant to encode an approximation to all eigenstates at once, which is a desirable property if one aims to calculate dynamical properties of local observables in MBL systems.…”
Section: Tensor Network Ansatzmentioning
confidence: 99%
“…It was suggested that the accuracy of the approximation for a given chain length can be increased by increasing the number of layers (the depth of the quantum circuit). Compared to the methods targeting eigenstates within an energy window [49][50][51][52], this procedure is constructed to efficiently represent all eigenstates with sufficient accuracy, providing access to dynamical properties of local observables.…”
Section: Introductionmentioning
confidence: 99%
“…We have proposed and analyzed the presumably simplest possible protocol for quantum magnets to exhibit the absence of ergodic dynamics, and thus Many-Body Localization in the form of remanent magnetization in initially ferromagnetically polarized antiferromagnets. The present calculation illustrates how the perturbative construction of conserved quantities allows one to make analytic predictions for quantities of experimental relevance.Our explicit recipe for constructing the conserved quantities is an analytical alternative to several recent numerical schemes based on DMRG [41][42][43][44] or quantum Monte Carlo [45] that allow one to study properties of specific MBL eigenstates. Since the simple formula (6) is derived under the sole assumption that the conserved operators have spectrum ±1, it could be applied to the conserved pseudo-spins constructed numerically in Refs.…”
mentioning
confidence: 99%
“…Our explicit recipe for constructing the conserved quantities is an analytical alternative to several recent numerical schemes based on DMRG [41][42][43][44] or quantum Monte Carlo [45] that allow one to study properties of specific MBL eigenstates. Since the simple formula (6) is derived under the sole assumption that the conserved operators have spectrum ±1, it could be applied to the conserved pseudo-spins constructed numerically in Refs.…”
mentioning
confidence: 99%